Pengaruh Faktor Pendidikan, Motivasi, dan Pengalaman Kerja terhadap Kinerja Perangkat Desa di Kecamatan Mranggen Kabupaten Demak - Suprihono Setyawan (Jurnal Ekonomi dan Bisnis Kontemporer, 2018)
Abstract:This study aims to examine and analyze the Effect of Education Factor, Motivation andWork Experience on the Performance of Village Devices in Mranggen Subdistrict Demak DistrictThis research was conducted by population method and carried out on 5 village officials in eachvillage Se District Mranggen Technique testing data used in this study include validity test, reliabilitytest, regression analysis, t test and mediation test.The results of the analysis and discussion show that the Education, Motivation and Work Experiencerespectively positively affect the Performance of Village Devices in Mranggen District DemakDistrict.Keywords: Education, Motivation, Work Experience and Village Device Performance